A Study on the Application of Tropical Architecture in the Design of a Serviced Office in Medan Sunggal Sub-District (International Journal of Architecture and Urbanism, 2022)
The design of a rental office in the sub-district of Medan Sunggal is a design for a rental office located in one of the business centres in the city of Medan, precisely in the sub-district of Medan Sunggal with the theme of tropical architecture. The problem that business actors or novice freelancers often face when trying to take independent steps to open new jobs due to Indonesia’s low level of employment is worrying about the high cost of office rentals like conventional office rentals in general. This rental office implements a serviced office system (office ready to use) which aims to make it easier for tenants, especially in terms of finances. The settlement method used is the descriptive method used in the design based on analytical reasoning and empirical structural research, along with identifying things that support the method. The use of a tropical architectural theme refers to the climate of Medan, which tends to be tropical and can be utilized by maximizing energy savings from natural sunlight. This rental office is expected to be good news for business actors, freelancers, and stakeholders in overcoming problems regarding the need for rental offices in the Medan Sunggal sub-district.